(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, some sources related to the chemistry and medicine of the Muslim East in the Middle Ages and which are now considered the most important in these areas are researched. In particular, Ibn an-Nadim’s "Kitab al-Fihrist al-’ulum" ("The Book of the Bibliography of Sciences"), "Tarikh al-Baghdad" ("History of Baghdad") by Al-Khatib al-Baghdadi ), Ibn al-Qifti’s "Ikhbar al-ʿulamoʾ bi akhbar al-hukamo" ("The Book of Acquainting Scholars with Information About Judges"), "ʿUyun al-Anbaʾ fi Tabaqat al-Atibbo" ("The Categories of Doctors" by Ibn al-Usaybi’a some comments about his works named "main messages about".